2018
DOI: 10.7717/peerj.4501
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive low intensity magnetic field stimulation in a neuronal cell line: a metabolomics study

Abstract: Low intensity repetitive magnetic stimulation of neural tissue modulates neuronal excitability and has promising therapeutic potential in the treatment of neurological disorders. However, the underpinning cellular and biochemical mechanisms remain poorly understood. This study investigates the behavioural effects of low intensity repetitive magnetic stimulation (LI-rMS) at a cellular and biochemical level. We delivered LI-rMS (10 mT) at 1 Hz and 10 Hz to B50 rat neuroblastoma cells in vitro for 10 minutes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…All intensities: altered plasma metabolite profile, IPA analysis shows altered metabolic pathways. Glutamine processing and glutamate signalling pathway changes across all intensities Hong et al, (2018) n = 4–6 per group Rat, In Vitro B50 neuroblastoma cells B50 neuroblastoma 1 1 Hz, 10 Hz - 10mins 10 mT (2.2–2.4 mT) Metabolite Assay Changes in 18 metabolites detected. 1 Hz: ↓ 7 amino acids, and 5 other metabolites including cholesterol.…”
Section: Li-rtmsmentioning
confidence: 99%
See 1 more Smart Citation
“…All intensities: altered plasma metabolite profile, IPA analysis shows altered metabolic pathways. Glutamine processing and glutamate signalling pathway changes across all intensities Hong et al, (2018) n = 4–6 per group Rat, In Vitro B50 neuroblastoma cells B50 neuroblastoma 1 1 Hz, 10 Hz - 10mins 10 mT (2.2–2.4 mT) Metabolite Assay Changes in 18 metabolites detected. 1 Hz: ↓ 7 amino acids, and 5 other metabolites including cholesterol.…”
Section: Li-rtmsmentioning
confidence: 99%
“…LI-rTMS has been associated with changes to several metabolites. For example, in B50 rat neuroblastoma cells, an inhibitory neuron-like cell type, an in vitro assay assessed changes in 18 metabolites following a single session of LI-rMS and showed frequency-dependent changes ( Hong et al, 2018 ). 1 Hz stimulation had stronger effects than 10 Hz stimulation, with more metabolites significantly affected (12 vs. 9) and greater fold changes following 1 Hz stimulation ( Hong et al, 2018 ).…”
Section: Li-rtmsmentioning
confidence: 99%
“…In the present study, lipid damage could be by induction of oxidative imbalance due to chronic exposure, suggesting that chronic ELF-EMF exposure could be like a mild-stressor; this finding is supported by the increase levels in plasma corticosterone concentration and brain lipid peroxidation. Changes in lipid composition, could have deep effects on membrane function by affecting membrane-associated enzymes, receptors and ion channels [ 43 ]. In the present study, different effects of RS and ELF-EMF were found in different brain regions, we speculate that these effects may be mediated by specific mechanisms, like phospholipase [ 30 ] activation by ELF-EMF and genomic and non-genomic effects of glucocorticoids, but these observations deserve further research as has been suggested previously in clinical trials [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, high-frequency (HF: >5 Hz) stimulation results in facilitation of neuronal activities, whereas low-frequency (LF: <1 Hz) stimulation reduces neuronal activities [35] [36]. In a previous study, Hong et al [32] measured the depletion of metabolites, which may involve an increase in GABA release, and showed that stimulation at 1 Hz is stronger with respect to these effects than 10-Hz stimulation, but did not identify the frequency-dependent effect correlated with neuronal excitability. In addition, the low-intensity fields are too weak to directly trigger action potential and the neurochemical changes may thus not be immediate but rather cause an increase in excitability by reducing action potential threshold and increasing spike firing potential [31].…”
Section: Introductionmentioning
confidence: 98%
“…There is evidence that LIMS can modulate brain function in humans [12] and in animal models [24]; however, the cellular and molecular mechanisms underlying the therapeutic effects of LIMS remain poorly understood. A few in vitro and ex vivo studies have demonstrated that LIMS alters gene expression [25], intracellular calcium concentrations in non-neuronal cells [26] [27] [28] and neuronal cells [29], neurobiological changes [30], neuronal excitability [31], and cellular metabolic and biochemical profiles [32]. However, it is still unknown whether LIMS provides facilitation or suppression effects depending on the stimulation protocol.…”
Section: Introductionmentioning
confidence: 99%